Experimental and Numerical Process Design for Press Partitioning of the New Q&P Steel 37SiB6 - Christian Illgen; Sven Winter; Rico Haase; Marcus Böhme; Nadja Reiser; Ansgar Hatscher; Verena Psyk; Verena Kräusel; Martin F.-X. Wagner (Metals, 2023)
Quenching and partitioning (Q&P) heat treatments of low-alloy steels with exceptional property combinations are particularly promising. In this study, we characterize for the first time a new low-alloy steel to be processed using Q&P heat treatments. In combined experimental and numerical studies, we design a novel approach that effectively combines the short cycle times of press hardening with the excellent property profiles of Q&P-treated steels. We identify an appropriate austenization temperature of 950 °C and a portioning temperature of 250 °C for Q&P heat treatments through dilatometric studies. We adjust a number of reference conditions with fractions of 2.1 to 6.3 wt.% of retained austenite, resulting in tensile strengths up to 1860 MPa and elongations to failure up to 7%. Initial numerical designs of the process can identify varying temperature profiles and cooling rates depending on the position in the die. The results show that the geometry of the part plays a minor role, but the die temperature of 200 °C is the dominant factor for successful partitioning directly in the press hardening process.